PERAN KARYAWAN DALAM MENINGKATKAN JUMLAH NASABAH PADA KSP NUSA ABADI - Sari Dewi, Komang Trisna; Cahyani, Ni Wayan; Dewi Kartika, Riana (Widya Amerta, 2025)
This study aims to determine how the influence of the Availability of Infrastructure Facilities, Provision of Incentives, and Promotion of Positions on Employee Performance at the Transportation Office of Buleleng Regency. This study uses a quantitative approach with the data collection technique used is a physical questionnaire and is assisted by Civil Servants of the Buleleng Regency Transportation Office. The measuring instrument used in the questionnaire is a Likert scale of 1-5. The selection of respondents used the Saturated Sampling method, namely the sampling technique as a whole from the total population, which was selected to be the respondent in this study were all Civil Servants at the Transportation Office of Buleleng Regency with a total of 82 Civil Servants. The data analysis technique used in this research is the SPSS version 18 model. The results showed that the Availability of Infrastructure Facilities, Provision of Incentives, and Position Promotion had a positive and significant effect on Employee Performance at the Transportation Office of Buleleng Regency.